CORRELATION BETWEEN AGE, WEIGHT AND BODY MEASURES AT FIRST PREGNANCY OF NELLORE HEIFERS - Abud, Lucas Jacomini; Abud, Cátia Oliveira Guimarães; Costa, Gustavo Lage; Fioravanti, Maria Clorinda Soares; Martins, Carlos Frederico; Pimentel, Concepta Margaret McManus; Sereno, José Robson Bezerra (Archives of Veterinary Science, 2018)
The objective of this study was to characterize and correlate weight, body condition and morphometric measurements with the beginning of the reproductive life in heifers of the Nellore breed. To determine the age of first pregnancy, 56 heifers of the Nellore breed were exposed to bulls. The females were evaluated for weight, body condition and body measurements every two months, from 16 to 32 months of age. The body measurements were: withers height, rump height, body length, head length, rump length, ear length, distance between ribs, distance from dorsal spine to belly, distance from ground to belly, head width, rump width, distance between ischiums, ear width, cannon bone perimeter, tail implantation perimeter, and thoracic perimeter. The results show that the animals had an average weight of 334±39 kg and an average age of 29±3 months at first pregnancy. The morphometric measurements of withers height, rump height, body length, rump length, head width, rump width, width between ischiums, tail implantation perimeter and thoracic perimeter were significantly greater in the pregnant animals. Can conclude from these results that a relationship between morphometric measurements and the first pregnancy in Nellore heifers.